PENGEMBANGAN BUKU POP-UP KULINER SEBAGAI UPAYA PROMOSI WISATA KULINER KOTA PEKALONGAN - Anisha Alfaticha; Sari Utari; Habibatus Salimah; Inayatul Ulya (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2019)
The promotion which was done by the owner of culinary tourism included 10 % using radio, 20 % private television, 10% social media, and 60 % no promotion. Knowing this condition, in this research the researchers aimed to develop pop -up book as media to promote Pekalongan culinary. This research used Research and Development design. It was done in 9 Pekalongan culinary tourist resort, they are Warung Mbak I bah Sorogenen, Pak Bon Sorogenen, Kopi Tahlil Pak Usman, Garang Asem Masduki, Sekoteng Pak Woh, Tauto Bang Dul dan Rohmani, Mie So Krapyak, Oriental Nyonya Silhuet, Gulai Kacang Ijo Pak Boy dan Pak Leman, Es Durian Merak dan Keripik Tahu Pusat Oleh-Oleh Pekalongan. The researchers did exploration to get the information of culinary menus and their history from the owner, next it was continued by making design and prototype. After that, the prototype was validated by the head of Tourism, Culture, Youth, and Sport Minis try. After doing the revision, the product of “Jelajah Kuliner Kota Pekalongan’ pop-up books were printed and published. The researchers gave recommendation to the Pekalongan government to use this pop -up book in introducing Pekalongan culinary to students and societies. In addition, this pop-up book can be used as media in promoting Pekalongan culinary through annual exhibitions. Keyword: Development, Pop-up, Tourism, Culinary